Sōzein ta phainomena: a herança da astronomia antiga no método da Ética Eudêmia de Aristóteles - Oliveira, Mariane Farias de (2018)
The present work aims to analyse the conception of phainomena, derived from ancient astronomy, in Aristotle's method and, more specifically, in the method of Eudemian Ethics. Our objective is to arrive, with this analysis, to a more precise conception about the method of the Eudemian Ethics, clarified, in this way, from a better understanding of the notion of phainomena - this understanding that permeates the work.